Kingianin A: A new natural pentacyclic compound from Endiandra kingiana - Leverrier, A.; Dau, M.E.T.H.; Retailleau, P.; Awang, Khalijah; Gueritte, F.; Litaudon, M. (American Chemical Society, 2010)
A new natural pentacyclic compound, named kingianin A, was isolated as a racemic mixture from the barks of Endiandra kingiana (Lauraceae). Its structure was elucidated by comprehensive analysis of NMR spectroscopic data, X-ray crystallography, and ECD calculations. The pentacyclic skeleton may be formed by a Diels-Alder reaction between two monomers having a bicyclo[4.2.0]octadiene backbone formed by a stereospecific electrocyclization of a linear compound of polyketide origin.